Grounding E-Government in Vietnam: From Antecedents to Responsive Government Services - Nguyen , Tuyen Thanh; Schauder , Don (Journal of Law and Governance, 2007)
The paper concerns the antecedents or preconditions for the successful development of e-government in Vietnam. The main antecedent issue under consideration is the readiness of the population to access and use networked ICTs, the prime communication medium of e-government. The paper reports the results of in-depth interviews with 38 citizens in various regions of the country. Its purpose is primarily to examine the capacity of citizens to become effective users of e-government services in terms of their access to, and capacity to use, ICTs. Its subsidiary purpose, in the light of these user-centric considerations, is to offer some thoughts on how government in Vietnam might position itself better to provide effective e-government services. In essence the paper attempts to shed light on the following questions: How ready is the population to make use of e-government services if these were provided? How ready is government to provide a full range of e-government services to this population? At present only 16 million out of Vietnam’s more than 85 million people are ICT/Internet users. If e-government service delivery is to be effective, clearly a much greater proportion of the population needs to become users. The paper looks at case studies of users and non-users, as well as background data from a variety of Vietnamese and international sources, in order to frame initial suggestions about how barriers to wider internet use can be overcome, and how services to current and future users could be made more effective.